INVESTIGATION OF MODULATION SCHEME AND TRANSMITTER NONLINEARITY IMPACT ON ADS-B MESSAGES TRANSMISSION VIA OFDM SATELLITE LINK - Kharchenko, Volodymyr; Bo, Wang; Grekhov, Andrii; Bezsmertna, Daria (Proceedings of National Aviation University (archive), 2014)
For investigation of modulation scheme impact on ADS-B messages transmission via satellite link the original model of a communication channel "Aircraft-to-Satellite-to-Ground Station" was built using MATLAB Sіmulіnk. Model consists of a source of information, aircraft transmitter, uplink/downlink path, satellite transponder, ground station receiver. The dependencies of a signal to noise ratio on free space path loss for different types of modulation (BPSK, QPSK, 16QAM, 64QAM), for different satellite transponder noise temperatures, channel bandwidth, number of OFDM symbols and different types of aircraft transmitter nonlinearity were received and investigated.